Efeitos espaciais e ambientais sobre a distribuição e diversidade beta de peixes em riachos da bacia do Alto Rio Paraná, Brasil - Souza, Thiago Henrique Lapa Oliveira (2014)
We aimed to evaluate whether variation in stream fish community composition is better explained by environmental factors, spatial factors or by both, over local and regional scales. We also analyzed whether fish beta diversity among basins is related to spatial extent and environmental heterogeneity and how species composition dissimilarity relates to geographic and environmental distances. It is hypothesized that the variation in species composition (raw data approach) would be more related to environmental factors within watersheds (at local scale) and that spatial filters would have increased importance when the analysis are run for the whole basin at scale (at regional scale). Considering the dissimilarity in species composition variation (distance data approach) it’s expected that the species dissimilarity would be higher among distant sites than among closer sites, while sites environmentally similar present similar species composition. For the beta diversity we expected the higher values to be found at microbasins with higher environmental heterogeneity and spatial extent. To obtain the spatial variables we used an eigenfunction analysis, called principal coordinates of neighbour matrices (PCNM) using overland distances. Most relevant spatial and environmental factors to explain fish composition variation were determined by the partial redundancy analyses (pRDA), followed by a variation partition method to estimate the exclusive fractions of each set of variables. Fish beta diversity, environmental heterogeneity and spatial extent values were calculated by the homogeneity of multivariate dispersions analysis between groups (PERMDISP). The partial Mantel's test was used to assess spatial and environmental dependency over species dissimilarity. The partition of variances demonstrated that fish community for the whole High Parana River basin was explained both by environmental factors (adjR2=0.08) and by spatial filters (adjR2=0.08). Stream fish species dissimilarity for the whole High Parana River basin was related to environmental distances, although geographic distances influence was two times more important than the effect caused only by the environment distances. Most sub-basins and microbasins biological distances had no relation to geographical or environmental distances. Also, there were no relation between fish beta diversity and environmental heterogeneity with spatial extent. Beta diversity presented a negative relation to the effect size (Mantel r) of environmental distances over composition dissimilarities, but the spatial extent and environmental heterogeneity had no influence over the effect of geographical or environmental distances over composition dissimilarity. Our study pointed out significant effects of the spatial structure (e.g dispersion, spatial distance and environmental control (e.g. species sorting) on stream fish assemblage distribution in Upper Paraná River basin. However, the geographical distance effect was more important to fish assemblage dissimilarities than the environmental distance only. Microbasins environmental heterogeneity and beta diversity were important to fish species similarity patterns in relation to geographical distance. Tough, fish beta diversity was not related to streams spatial extent and environmental heterogeneity.